Religious Moderation in Anticipation of Religious Politicization ahead of The 2024 Election - Erti Fadhilah Putri; Khairul Umam Manik (Journal of Current Research in Management, Policy, and Social Studies, 2024)
The elections and local elections in 2024 are still about two years away. However, anticipation is needed so that the 2024 elections can be held safely. Based on the pattern of elections and local elections, which usually are filled by identity politics and lead to massive violence. This study aims to explain the challenges of vulnerability that Indonesia will face in the implementation of the 2024 elections and local elections. This study uses qualitative research methods with primary and secondary data sources obtained from verified and relevant sources for research. The findings found are the potential for polarization from the use of identity politics in the 2024 election, the widespread use of social media accelerates the polarization that occurs in society, and religious moderation is the answer in anticipating the use of identity politics in the administration of elections. With the community's involvement, the work scheme of religious moderation can be a tool to anticipate the politicization of religion.